Power shaping control of DC–DC converters with constant power loads. (December 2020) - Mayo-Maldonado, J.C.; Ruiz-Martinez, O.F.; Escobar, G.; Maupong, T.M.; Valdez-Resendiz, J.E.; Rosas-Caro, J.C.
Abstract: This paper deals with the stabilization of DC–DC converters feeding constant power loads (CPLs). It is shown that power/energy dynamics are easily computed via the image of the input/output voltages/currents of the converter. Such image is represented by a high-order differential operator, obtained from first principles, acting on the variables of a stabilizing interconnected controller. This approach is based upon the premise that the destabilizing effect of CPLs, is caused due to a power imbalance in a dissipation equality, which prevents passivity. The proposed stabilizing mechanism shapes the power dynamics via an interconnected controller, inducing a feasible power flow and thus passivity. To do so, we developed a stability test, as well as control design tools in terms of linear matrix inequalities (LMIs), constructed from coefficient matrices of the system dynamics. As a practical advantage, the proposed power shaping approach permits to link stability conditions with the nominal power rate specification of power converters. Finally, we show that the proposed framework can also accommodate other traditional frequency domain, eigenvalue and immittance criteria. The main results are validated via a theoretical analysis and experimental results. Highlights: A high-order linear differential approach to control DC–DC converters is introduced. The issue of instability induced by active constant power loads is addressed. Stability is guaranteed via a Lyapunov approach. Behavioral system theory is the pivotal figure for the analysis. Experimental results using a DC–DC converter feeding a constant power load are presented.